2018
DOI: 10.1371/journal.pone.0191547
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced alterations in redox homeostasis and oxidative stress are present from an early age

Abstract: ObjectivesOxidative stress and inflammation have been postulated as underlying mechanisms for the development of obesity-related insulin resistance. This association however, remains elusive especially in childhood. We sought to investigate this relation by measuring oxidative stress and antioxidant response biomarkers, before and during an oral glucose tolerance test (OGTT), in different biological samples from obese children.Subjects24 children were recruited for the study, (18 obese and 6 controls). After O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 36 publications
10
39
0
1
Order By: Relevance
“…32,33 It has been shown that MDA increases in obese patients compared to healthy people. 34,35 In the present study, the levels of LPO among subjects with normal weight, overweight, and obesity were similar. This result could be related to the fact that dyslipidemia was homogeneously distributed between groups.…”
Section: Discussionsupporting
confidence: 64%
“…32,33 It has been shown that MDA increases in obese patients compared to healthy people. 34,35 In the present study, the levels of LPO among subjects with normal weight, overweight, and obesity were similar. This result could be related to the fact that dyslipidemia was homogeneously distributed between groups.…”
Section: Discussionsupporting
confidence: 64%
“…Recent study demonstrated that in obesity conditions the alterations in redox homeostasis and oxidative stress are present from an early age, as indicated by an increase in MDA content and GSH/GSSG ratio [38]. Malondialdehyde (MDA), an important biomarker of oxidative stress, is generated by the peroxidation of lipids containing polyunsaturated fatty acids and is cytotoxic due to its ability to induce macromolecular crosslinking polymerization [39].…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, obesity-related insulin resistance provides a potential link between trans-βcarotene and obesity. Obese children with insulin resistance suffer an additional oxidative stress and thus, their antioxidant mechanisms become overwhelmed and struggle to manage acute stressors [38]. The main feature of β-carotene is its low polarity and large number of double bonds, which contribute to its powerful antioxidant properties [39].…”
Section: Discussionmentioning
confidence: 99%